The INFLUENCE OF GAMIFICATION ON BRAND LOYALTY : A STUDY OF A DIGITAL BANK IN INDONESIA WITH CUSTOMER ENGAGEMENT AS MEDIATION - Tampubolon, Abram Myhero Yancristofel; Sari, Diana (Journal of Business Studies and Management Review, 2025)
This research examines how gamification affects brand loyalty, emphasizing the mediating function of customer engagement within the context of a digital banking application. Utilizing data from 323 respondents and employing Partial Least Squares Structural Equation Modeling (PLS-SEM), the study demonstrates that gamification positively influences both customer engagement and brand loyalty. Additionally, customer engagement serves as a partial mediator, indicating that users who are engaged cognitively, emotionally, and behaviorally tend to exhibit stronger brand loyalty. These findings underscore the strategic importance of gamification in enhancing engagement and cultivating lasting customer relationships in the digital banking sector.